Nanoscale Pore Characteristics of the Lower Permian Shanxi Formation Transitional Facies Shale, Eastern Ordos Basin, North China - Wang, Zhanlei; Guo, Bingzheng; Jiang, Chan; Qi, Lin; Jiang, Yuqiang; Gu, Yifan; Fu, Yonghong; Liang, Demin (Frontiers in Earth Science, 2022)
The Lower Permian Shanxi Formation in the Eastern Ordos Basin is a set of transitional facies shale, and it is also a key target for shale gas exploration in China. Based on lithofacies classification by X-ray diffraction and kerogen type identification, nanoscale reservoir space, pore volume, pore size distribution, surface area, and fractal characterization were studied using comprehensive methods including N2 and CO2 adsorption, mercury injection capillary pressure, field emission-scanning electron microscopy (FE-SEM), and nuclear magnetic resonance. The results indicate that Shanxi Formation shale can be subdivided into five types of lithofacies: clayey shale (lithofacies I), siliceous clayey shale (lithofacies II), siliceous shale (lithofacies IV), calcareous siliceous shale (lithofacies V), and siliceous calcareous shale (lithofacies VI). Lithofacies V and lithofacies VI are the best lithofacies in terms of organic pore morphology, connectivity, and development degree, followed by lithofacies II. Inorganic pores and microfractures are well developed in all lithofacies. The majority of pores in lithofacies I comprise organic mesopores, but pore volume is contributed by a few inorganic macropores. The pore types and pore volume contributors of lithofacies II are organic macropores. The pore size distribution of lithofacies IV is very similar to that of lithofacies I. The pore size distribution of lithofacies V shows typical bimodal characteristics. It is suggested that the inorganic pores of lithofacies V are mainly macropores, which have the greatest contribution to pore volume, followed by organic mesopores. Total organic carbon (TOC) and thermal maturity do not present obvious controls on pore structure. Vitrinite is the main kerogen type in lithofacies II and IV, and this is associated with disfavored morphology, low connectivity, and poor development degree of organic pores. In contrast, sapropelinite is observed in other shale lithofacies, and it is suggested to be an effective kerogen type that contributes to better development of organic pores.